(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Dental caries is a highly prevalent biofilm-mediated disease arising from complex interactions among oral microorganisms, diet, saliva, and host factors. Saliva is increasingly recognised as a practical and informative matrix for characterising oral microbial ecology and identifying biomarkers of caries risk. This narrative review synthesises historical and contemporary evidence on the salivary microbiome in caries research, with three aims: (a) to highlight early yet foundational work on salivary mutans streptococci and host factors, (b) to critically examine similarities and differences among recent 16S, metagenomic, and multi-omics studies linking salivary communities to caries, and (c) to discuss key future directions and translational potential. Early culture-based studies established strong associations between high salivary Streptococcus mutans counts, low pH, and elevated caries experience, supporting saliva-based microbial screening as a feasible risk assessment tool. More recent microbiome-era work reveals broader salivary dysbiosis in caries, involving shifts in community composition, functional pathways, and host–microbe interactions, although findings beyond S. mutans vary across age groups, populations, and methodologies. Metagenomic and metabolomic analyses demonstrate that specific taxa, pathways, and salivary proteins and metabolites can serve as candidate biomarkers, and that salivary parameters, including flow rate and pH, significantly modulate microbial signatures. Nevertheless, progress is limited by methodological heterogeneity, reliance on cross-sectional designs, and under-representation of multi-kingdom and multi-omics integration. Future research priorities include protocol standardisation, longitudinal cohort studies, mechanistic multi-omics, identification of protective taxa, and application of machine learning to multi-dimensional salivary datasets. Ultimately, salivary microbiome research holds promise for precision caries prediction and minimally invasive, microbiome-informed prevention strategies that can be applied in personalised care as well as in wider public health programmes.